2020
DOI: 10.3892/or.2020.7706
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA PVT1 promotes tumor cell proliferation, invasion, migration and inhibits apoptosis in oral squamous cell carcinoma by regulating miR‑150‑5p/GLUT‑1

Abstract: Oral squamous cell carcinoma (OSCC) is a cancer with high morbidity and mortality. Research has demonstrated that long non-coding RNAs (lncRNAs) are critical for tumor initiation and development. In the present study, we aimed to ascertain the functions and potential mechanisms of lncRNA plasmacytoma variant translocation 1 (PVT1) in OSCC. Firstly, we found that the expression of PVT1 was increased in human OSCC tumor tissues and it was related to reduced survival of the patients. Furthermore, miR-150-5p expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Hsa-miR-150-5p participates in the regulation of various cancers, including breast cancer, colorectal cancer, and oral squamous cell carcinoma (OSCC) [ 8–10 ]. For instance, hsa-miR-150-5p expression was dramatically decreased in OSCC tissues, which further repressed cell growth and enhanced apoptosis of OSCC cells [ 10 ]. Additionally, hsa-miR-150-5p expression is downregulated in breast cancer tissues and attenuates the proliferation and migration of breast cancer cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hsa-miR-150-5p participates in the regulation of various cancers, including breast cancer, colorectal cancer, and oral squamous cell carcinoma (OSCC) [ 8–10 ]. For instance, hsa-miR-150-5p expression was dramatically decreased in OSCC tissues, which further repressed cell growth and enhanced apoptosis of OSCC cells [ 10 ]. Additionally, hsa-miR-150-5p expression is downregulated in breast cancer tissues and attenuates the proliferation and migration of breast cancer cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“… 95 In another study also focusing on OSCC, researchers have shown that, by regulating miR-159-5p and GLUT-1, the lncRNA PVT1 promotes tumor cell proliferation, invasion, and migration, and inhibits apoptosis of cancer cells. 96 Furthermore, Yang et al. have suggested that lncRNA H19 could promote glycolysis pathway in CAFs, thus accelerating the growth of OSCC through the H19/miR-675-5p/6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 axis.…”
Section: Mechanism Of Lncrnas In Hnsccmentioning
confidence: 99%
“…LncPVT1 promotes laryngeal squamous cell carcinoma cell proliferation, migration, and anti-apoptosis by acting as a molecular sponge to regulate miR-519d-3p (139). In addition, lncPVT1 competitively combined with miR-150-5p to regulate GLUT1, thereby promoting the proliferation, migration, invasion, and antiapoptosis of oral squamous cell carcinoma (140). LncPVT1 overexpression promoted HNSCC growth, significantly reduced the apoptosis rate of HNSCC cells treated with cetuximab, and reduced the drug sensitivity of HNSCC cells.…”
Section: Lncpvt1 and Resistance To Other Drugsmentioning
confidence: 99%